Lien Rights: The Invisible Pillar Urgently Needed in Indonesia’s Construction Security System Regulation - Gianina Elizabeth Adiwinata; Yohanes Sogar Simamora; Faizal Kurniawan; Patricia Anais Aristyawan; Xavier Nugraha (Universitas Internasional Batam, 2025)
Indonesia’s construction sector faces acute payment risk, particularly for subcontractors and suppliers positioned downstream in multi-tier contractual chains. Unlike many common law jurisdictions that mitigate this risk through statutory construction lien rights, non-possessory security interests that attach to the improved aset, Indonesia lacks an equivalent construction-specific proprietary protection, leaving payment security largely dependent on contract remedies and general security devices. This article examines (i) how construction lien regimes function as project-specific security mechanisms in selected common law jurisdictions and (ii) the normative and functional gap created by their absence in Indonesia, along with feasible accommodation pathways. Employing doctrinal (normative) legal research using statutory, conceptual, and comparative approaches, the study analyzes representative lien frameworks in North Dakota, Texas, and Ontario. The analysis finds that, despite jurisdictional variations, lien regimes share a regulatory core: lien rights arise upon performance, are made transparent through notice/registration systems, operate under calibrated priority rules, and are enforceable against the project asset through structured procedures. By contrast, Indonesia’s principal security instruments, Mortgage Rights (Hak Tanggungan) and Fiduciary Security (Jaminan Fidusia), are structurally ill-suited to secure progressively embedded construction value and to protect parties lacking privity with owners. The article concludes that strengthening Indonesia’s construction security framework requires a construction-specific proprietary mechanism, preferably statutory recognition of construction lien rights with carefully designed registration, time limits, and priority rules to balance contributor protection with owner and financier certainty.